Investigating the role of mobile payment quality characteristics in the United Arab Emirates: implications for emerging economies. Issue 7 (7th September 2020) - Mouakket, Samar
Abstract : Purpose: This study contributes to the limited and rather fragmented research on mobile payment (m-payment) within a post-adoption context by identifying individual characteristics (personal innovativeness and m-payment self-efficacy) and m-payment quality characteristics (system quality, information quality and service quality) that can influence expectations about performance and effort of this technology. These two outcome expectations may affect user satisfaction with m-payment, which will in turn influence users' continued intention to use this technology. Design/methodology/approach: A survey was carried out among university students in the United Arab Emirates who have used the m-payment method. Structural equation modeling technique was used to test and analyze both the measurement model and the structural model. Findings: Individual characteristics are important in establishing users' expectations of the ease of use and usefulness of m-payment. However, of the quality characteristics, only system quality significantly affected users' expectations of the ease of use and usefulness of m-payment. Originality/value: The findings of this study provide unique insights into the individual and quality characteristics that will eventually lead to continued intention to use m-payment. This will help businesses to develop appropriate marketing strategies to increase adoption and use of m-payment.